Queijo minas padrão com reduzido teor de sódio: composição e caracterização sensorial - Santos, Thaís Gentiluce dos (2015)
Sodium is an essential nutrient with important functions in the organism, however, its ingestion in excess may cause various health problems such as arterial hypertension, brain diseases, heart failure and chronic renal failure. In this context, the present study proposes to prepare Minas Padrão cheese with different contents of sodium with the objective of evaluating the effect of the addition of potassium chloride in sensory characteristics and hysicochemical properties, as well as in the proximal composition and in microbiological quality. The cheeses were elaborate in concentrations of 100% of NaCl (C), 80% of NaCl + 20% of KCl (T1), 60% of NaCl + 40% of KCl (T2), 40% of NaCl + 60% of KCl (T3) and 20% of NaCl + 80% of KCl (T4) and stored for 20 days at 10 ºC. The proximal composition and physicochemical was based on the determination of moisture content, fat, protein, ash, chloride, sodium, potassium, titratable acidity and pH of all treatments after 20 days of storage. The microbiological quality of the samples was monitored through the count of Total Coliforms and Escherichia coli, Staphylococcus aureus, Salmonella spp., mold and yeast in the first and fifteenth day of storage. The sensorial characterization was performed by the technique of Free Profile choice. The results showed that the replacement of sodium chloride by potassium in the Minas Padrão cheese in concentration higher than 40% presented significantly higher moisture contents. Cheese with a reduction greater than 60% of sodium obtained significantly effect in the titratable acidity, presenting higher values compared to the other treatments. The cheese with 20% of salt replacement did not differ statistically in relation to the control. When the proportion of substituent was increased, a significant reduction of the sodium content of up to 73% was observed. As the sodium was replaced by potassium in cheese, the potassium content increased significantly, stablishing a reduction of 82% in relation to the control. There was no effect to sodium substitution by potassium in fat, protein, ash and chlorides, as well as the pH values. The microbiological results were in accordance with the current legislation, therefore suitable to be eaten. According to the Free Profile Choice technique it was observed that the control C cheese (100% of NaCl) showed results very close to the other treatments, differing only in flavor attributes. The replacement of sodium by potassium in proportions of 20% contributed to a bitter taste detected by the tasters. Whereas, the appearance, flavor and texture attributes showed no significant differences compared to the Minas Padrão cheese.